Self-assembled anchor layers/polysaccharide coatings on titanium surfaces: a study of functionalization and stability - Pop-Georgievski, Ognen; Kubies, Dana; Zemek, Josef; Neykova, Neda; Demianchuk, Roman; Chánová, Eliška Mázl; Šlouf, Miroslav; Houska, Milan; Rypáček, František (Beilstein Journal of Nanotechnology, 2015)
Composite materials based on a titanium support and a thin, alginate hydrogel could be used in bone tissue engineering as a scaffold material that provides biologically active molecules. The main objective of this contribution is to characterize the activation and the functionalization of titanium surfaces by the covalent immobilization of anchoring layers of self-assembled bisphosphonate neridronate monolayers and polymer films of 3-aminopropyltriethoxysilane and biomimetic poly(dopamine). These were further used to bind a bio-functional alginate coating. The success of the titanium surface activation, anchoring layer formation and alginate immobilization, as well as the stability upon immersion under physiological-like conditions, are demonstrated by different surface sensitive techniques such as spectroscopic ellipsometry, infrared reflection–absorption spectroscopy and X-ray photoelectron spectroscopy. The changes in morphology and the established continuity of the layers are examined by scanning electron microscopy, surface profilometry and atomic force microscopy. The changes in hydrophilicity after each modification step are further examined by contact angle goniometry.
Keywords: alginate; biomimetic surfaces; bisphosphonates; neridronate; poly(dopamine); spectroscopic ellipsometry; surface characterization; surface modification; titanium; XPS